Variasi Pola Sidik Jari dan Pola Palmar pada Masyarakat Suku Rejang Bengkulu - Resiliani, Tiara; Kamilah, Santi Nurul; Lestari, Dian Fita; Jarulis, Jarulis; Sipriyadi, Sipriyadi; Muslim, Choirul (Universitas Medan Area, 2023)
The Rejang tribe is one of the indigenous communities in Bengkulu. They are dispersed throughout several areas of Bengkulu, however, the majority of them live in the Rejang Lebong district. The Rejang tribe is classified as a Malayan Mongoloid race. Generally, every tribe has distinctive characteristics. These characteristics include language, culture, religion, and physical characteristics. The purpose of this study was to analyze the characteristics of the Rejang tribal community residing in Pematang Sapang village, North Bengkulu, with a focus on their fingerprint and palm patterns. Data was gathered from 100 individuals of the Rejang tribe, who fulfilled the inclusion criteria. The data was analyzed quantitatively. The study determined that there are three fingerprint patterns in the Rejang community, with the loop pattern being most prevalent at 59.8%. There are only two palmar patterns; normal and simian, with the normal pattern being dominant at 94.5%. Statistical analysis revealed no significant correlation between fingerprint or palmar patterns and sex. Furthermore, there was no observable relationship between fingerprint and palmar patterns. The Rejang tribe is characterized by the prevalence of the loop patterns for fingerprints and the normal patterns for palmar.